Primordial Biochemicals Within Coacervate-Like Droplets and the Origins of Life - Stefano, George B; Kream, Richard M (Viruses, 2025)
An organism is considered "alive" if it can grow, reproduce, respond to external stimuli, metabolize nutrients, and maintain stability. By this definition, both mitochondria and viruses exhibit the key characteristics of independent life. In addition to their capacity for self-replication under specifically defined conditions, both mitochondria and viruses can communicate via shared biochemical elements, alter cellular energy metabolism, and adapt to their local environment. To explain this phenomenon, we hypothesize that early viral prototype species evolved from ubiquitous environmental DNA and gained the capacity for self-replication within coacervate-like liquid droplets. The high mutation rates experienced in this environment streamlined their acquisition of standard genetic codes and adaptation to a diverse set of host environments. Similarly, mitochondria, eukaryotic intracellular organelles that generate energy and resolve oxygen toxicity, originally evolved from an infectious bacterial species and maintain their capacity for active functionality within the extracellular space. Thus, while mitochondria contribute profoundly to eukaryotic cellular homeostasis, their capacity for freestanding existence may lead to functional disruptions over time, notably, the overproduction of reactive oxygen species, a phenomenon strongly linked to aging-related disorders. Overall, a more in-depth understanding of the full extent of the evolution of both viruses and mitochondria from primordial precursors may lead to novel insights and therapeutic strategies to address neurodegenerative processes and promote healthy aging.
Keywords: biologická evoluce; viruses; reaktivní formy kyslíku; Viruses; Reactive Oxygen Species; energetický metabolismus; Animals; Biological Evolution; původ života; Humans; mitochondrie; mitochondria; viry; coacervate droplets; zvířata; evolution; Origin of Life; bacteria; reactive oxygen species; environmental DNA; lidé; Energy Metabolism; Mitochondria